Profil Peresepan Analgetik Antipiretik di UPT Puskesmas X Kabupaten Tanah Datar - Renatalia Fika; Muhajri Agusfina; Mevy Trisna; Budi Setiawan; Yulia Ningsih (Journal Pharma Saintika, 2024)
This study analyzed the prescription profile of Analgesics - Antipyretics at the X Health Center UPT, Tanah Datar Regency in 2022 with retrospective data from 600 patient prescriptions. The results showed the highest use of Analgesics - Antipyretics in the adult age group (26-45 years) at 27.80% and the lowest was in the children's age group (5-11 years) at 17.50%. More women (50.83%) used Analgesics - Antipyretics than men (49.17%). Paracetamol tab 500mg was the most frequently prescribed type (66.67%), followed by Paracetamol syrup (16.83%) and Ibuprofen 400 mg (16.50%). This information is important for the X Health Center UPT to improve health services and more effective drug management. However, further research is needed to better understand the pattern of Analgesics - Antipyretics use in the area.